Public relations - Verčič, Dejan (Teorija in praksa, 2011)
Public relations emerged as an academic discipline in the 1980s in the US, and in 1990s it institutionalised itself in European academia as well. Work at the Marketing Communication and Public Relations department, Faculty of Social Sciences, University of Ljubljana, has been instrumental in the Europeanisation and globalisation of the predominantly US public relations theory and contributed to the development of the reflective model of public relations.
Keywords: Communication management; Komunikacijsko upravljanje; Odnosi z javnostmi; Public relations; Slovenia; Slovenija; strateško komuniciranje; tržno komuniciranje